PENGARUH PENCELUPAN KARKAS AYAM PEDAGING DALAM LARUTAN ASAM SITRAT DAN ASAM ASETAT TERHADAP ANGKA LEMPENG TOTAL Escherichia coli (The Immersion Effect of Broiler Carcass in Citric Acid and Acetic Acid on the Total Plates Count of Escherichia Coli) - Nurliana Nurliana; Sandy Cakra Yuda; Faisal Jamin; Teuku Reza Ferasyi; M. Isa; Darmawi Darmawi (Universitas Syiah Kuala, 2015)
This study aimed to determine the immersion effect of broiler carcasses in 3% citric acid, 3% acetic acid, and combination of citric acid and acetic acid with concentration of 1.5% each on the total plate count of bacteria E. coli. Eight broilers carcasses (dissected into 2 parts) were divided into 4 treatment groups with 2 times repetition and 3 times observation at 0, 4, and 8 hours after dipped. The control treatment (K0) without dipped into acid solution. Broiler carcasses in the first (K1), second (K2), and the third (K3) treatments were dipped into 3% acetic acid, 3% citric acid, and combination of 1.5% acetic acid and 1.5% citric acid respectively. Data were analyzed using analysis of variance. The average of E. coli count in K0 at 0, 4, and 8 hours post dipping were 5.2±0.061, 6.8±0.99, and 7.0±0.107 log 10 cfu/g of chicken meat respectively. In similar observation time with K0, the average of total E. coli count were 5.5±0.373, 6.0±0.023, and 6.0±0.242 log 10 cfu/g of chicken meat in K1, 5.3±0.166, 6.0±0.143, and 6.0±0.084 log 10 cfu/g of chicken meat in K2, 5.7±0.041, 5.9±0.92, and 5.8±0.058 log 10 cfu/g of chicken meat in K3 at 0,4, and 8 hours post dipping respectively. Statistical analysis showed that the immersion of broiler carcass in acetic acid and citric acid solution were significantly (P 0.05) decrease the number of E. coli. There were interaction between immersion of broiler carcass in organic acids and observation time which significantly decrease the number of E. coli (p 0.05). In conclusion, the immersion of carcass chicken in 3 % acetic acid, 3% citric acid, and their combination reduce the amount of E. coli. Key words: chicken carcass , citric acid 3%, acetic acid 3% , Escherichia coli